(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Many terms used in the system of terms used in the field of wastewater and its treatment system are distinguished by special signs. The terminology of the studied wastewater and its treatment system is mainly composed of terms borrowed from another language and combined into the meaningful field of "wastewater", which are important components of this field. The article also discusses the role of "Waste water and its treatment system terms" in the field terminology system.